Limb Laterality Discrimination, Evoked Sensations and Somatosensory Behavior in Fibromyalgia Syndrome: A Cross-Sectional Study - Víctor Riquelme-Aguado; Antonio Gil-Crujera; Josué Fernández-Carnero; Ferran Cuenca-Martínez; Francisco Gómez Esquer (Applied Sciences, 2022)
The main objective of this study was to assess the status of body schema using limb laterality discrimination tasks and pain measurement variables of patients with FMS compared to healthy subjects. The secondary aim was to analyze the relationships between laterality discrimination with respect to somatosensory variables. Thirty female patients with FMS (with a mean age of 52.43 ± 11.82 years) and thirty healthy women (with a mean age of 47.93 ± 5.92 years) were recruited. The main outcome measures were laterality discrimination, referral of evoked sensations, pressure pain threshold and conditioned pain modulation. The main analysis showed that patients with FMS have a longer reaction time for laterality discrimination in hands (hands—20 images, t = 4.044, p < 0.0001, d = 1.04; hands—50 images t = 4.012, p < 0.0001, d = 1.31; feet—20 images t = 2.982, p < 0.01, d = 0.76; feet—50 images, t = 2.159, p < 0.05, d = 0.55). With regard the secondary analysis, patients with FM have higher mechanical hyperalgesia (t = −9.550; p < 0.0001, d = 2.51) and decreased response to conditioned pain modulation compared with healthy subjects (t = 15.519; p < 0.0001, d = 4.17). A positive correlation was found in patients with FMS between greater laterality discrimination ability and better function of conditioned pain modulation (hands r = 0.676, p < 0.0001; feet r = 0.485, p < 0.01). In conclusion, patients with FMS have a longer reaction time and lower accuracy for laterality discrimination, increased mechanical hyperalgesia and decreased conditioned pain modulation compared to healthy subjects. Finally, it seems that there is a positive correlation between greater laterality discrimination ability and better conditioned pain modulation function.